The Multidimensional Stephan Klasen Exposure Index: Why Wonder woman should become a postdoc and wear white socks with sandals - Laura Barros; Liza von Grafenstein; Melanie Grosse; Sarah Khan; Friederike Lenel; Tatiana Orozco Garcia; Marcello Pérez-Alvarez; Manuel Santos Silva; Claudia Schupp; Holger Strulik (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2020)
"The job of a 'measure' or an 'index' is to distill what is particularly relevant for our purpose,and then to focus specifcally on that... That is not an easy task." Sen (1989). And that is precisely our aim. In this paper, a measurement for multidimensional exposure to Stephan Klasen is developed for the first time ever. We use our exposure measure to test theoretical predictions on its effects on worldview, life perspectives, and various welfare measures. In our sample, the exposure degree to Stephan Klasen varies signifcantly, with a slight majority identified as "exposed" according to our frst-of-its-kind Multidimensional Stephan Klasen Exposure Index. Our results show that being exposed to Stephan Klasen increases: 1) tolerance overall (and in particular towards macroeconomists, statisticians and people wearing socks with sandals), 2) preference of postdocs over PhDs in times of scarcity, 3) self-perceived wealth, and 4) a person's consciousness towards global problems such as inequality, poverty, and climate change. Furthermore, we show that specifc habits such as signing emails with initials, social media usage, and brushing teeth can partly explain the Stephan Klasen effect. The data allow us to draw some highly relevant policy conclusions. We conclude that while caution on the causal interpretation of our estimates is needed, our exercise confirms years of qualitative evidence which has unequivocally indicated the multidimensional benefits of being exposed to Stephan Klasen.
Keywords: D03; I31; 330; Habit formation; Multidimensional index; Role model